A Hindu Theology of Liberation: Not-Two is Not One, by Anantanand Rambachan. (4th August 2021) - Adluri, Vishwa
Abstract : A Hindu Theology of Liberation: Not-Two is Not One, by Anantanand Rambachan. Albany, NY: State University of New York Press, 2015. xi + 230 pp. £74.94 (hb), £23.50 (pb). ISBN 978-1-4384-5455-9 (hb), ISBN 978-1-4384-5456-6 (pb).